A morphologically atypical great fruit-eating bat Artibeus lituratus from Paraguay - Vrla, Sarah C.; Winnett, Morgan E.; Stevens, Richard D. (Therya Notes, 2023)
Morphological abnormalities and their underlying causes are well documented and understood in humans and some domesticated animals but are less often reported within wild populations. This is likely because many abnormalities lead to the early death of individuals and typically are only encountered within large samples of specimens. Here, we report an adult female great fruit-eating bat Artibeus lituratus (Chiroptera, Phyllostomidae) collected from Paraguay with notable skull and post-cranial abnormalities. Specimens, including the atypical A. lituratus, were collected from eastern Paraguay and prepared as skin and skull museum voucher specimens and deposited in the Natural Science Research Laboratory of the Museum of Texas Tech University. Sequences of Cytochrome b (Cyt b) were generated and uploaded to BLAST to confirm species identification. We then quantitatively compared the atypical individual with 15 typical females collected from the same locality using 13 wing measurements and 13 skull measurements. The Cyt b sequence of the atypical specimen was a 100 % match to A. lituratus. The atypical specimen was much smaller from the perspective of overall body size and wing morphology. The skull was also qualitatively different, much smaller and less robust than other female A. lituratus from this site. Mastoids and the sagittal crest were greatly reduced, and the frontal shield was absent in the atypical individual. We encourage reports of morphological abnormalities to be made as determining rates of abnormalities within populations may indicate their overall health.